Mental health curricula and Mental Health First Aid in the MPharm. (26th March 2021) - Gorton, H C; Macfarlane, H; Edwards, R; Farid, S; Garner, E; Mahroof, M; Rasul, S; Keating, D; Zaman, H; Scott, J; Maidment, I; Strawbridge, J
Abstract: Introduction: Improving mental health care is an international priority, and one that is championed by the Royal Pharmaceutical Society. (1) In the course of their work, pharmacists frequently encounter people with mental health problems. The extent to which mental health is taught on the undergraduate pharmacy degree in the UK and Ireland, and the inclusion of Mental Health First Aid (MHFA) training, has not be described recently. Aim: We aimed to determine how mental health teaching is embedded into the MPharm and students' perception of their own preparedness to help people with their mental health. We explored if and how MHFA training is included, and students' experience of, or desire to complete this. Methods: We conducted an anonymous, online questionnaire of UK and Ireland MPharm students, distributed via networks and social media. Students were asked a series of closed questions about mental health teaching in the MPharm, and exposure to MHFA. We analysed answers using descriptive statistics. We included some open-ended questions to enable students to expand on their answers. We used this qualitative data to contextualize findings. We invited one member of staff from each university to answer a modified staff version of the questionnaire, in order to provide a curriculum overview and staff perspective on MHFA provision. Results: 232 students and 13 staff responded, from 22 universities in total. Eighty percent of student participants were female and 70% were in the third or final year of study. Three-quarters of students felt that mental health was not embedded throughout the MPharm. Eighty-percent of students stated that they were taught about neuropharmacology and 44.8% stated that their course included communicating with people about their mental health. One third of students felt that their degree adequately prepared them to help people with their mental health. Twenty-six students (11.6%) had completed MHFA training of which 89% would endorse inclusion of this within the MPharm. Of those who had not completed the training, 81% expressed a desire to do so. Those who completed MHFA training self-reported more preparedness than those who did not, but student numbers were small. Conclusion: Mental health teaching remains focused on theoretical aspects, such as pharmacology, with less emphasis on practical skills, such as communication skills that might support interactions about mental health. MHFA was viewed by students as one way to enhance this. Of the small number of students who had completed MHFA, they displayed an increased self-reported preparedness. This could, however, be linked to the environmental culture of the programme rather than the training per se. MPharm programmes need sufficient focus on skills including communication and crisis response that may be required by pharmacists, alongside the fundamental scientific knowledge relating to mental health. References: 1. Royal Pharmaceutical Society. No health without mental health: How can pharmacy support people with mental health problems? London: RPS; 2018.